Effects of aloe vera gel application on epidermal wound healing in the domestic rabbit - Kayode, Olaifa Abayomi (International Journal of Research in Medical Sciences, 2016)
Background: A wound is a breakdown in the protective function of the skin or loss of continuity of epithelium, with or without loss of underlying connective tissues, muscles, nerves, bones following injury to the skin, surgery, a blow, cut, chemicals, heat, cold, friction, shear force, pressure or diseases such as leg ulcers or carcinomas. A study was undertaken to determine the healing properties of Aloe vera gel on epidermal wounds in rabbits. Methods: Twelve adult rabbits were divided into two groups randomly of six each representing the treatment and control respectively. A pair of wounds measuring 2cm x 2cm each was created on the back of each rabbit lateral to the spinal cord. The wounds were treated with homogenized Aloe vera gel while the wounds on control group were treated with normal saline. Wound contraction was measured on days 5, 9 and 12 representing the inflammatory, proliferative and maturation phases of wound healing respectively. Blood samples were collected on days 0, 3, 6, 9 and 12 for analysis. Results: Animals treated with Aloe vera gel had significantly (p<0.05) faster rates of healing with shorter days of scab fall off than the control and showed significant (P<0.05) changes in the packed cell volume, mean corpuscular volume, lymphocyte and neutrophil counts. Conclusions: The study concluded that Aloe vera was effective in treating epidermal wounds in rabbits over the control. An improvement occured in haematological profile of the experimental animals and these findings will go a long way in expanding the horizon of clinical application of this plant in solving wound healing problems in both humans and other animal species.